Congenital Plasmodium falciparum infection in neonates in Muheza District, Tanzania - Kimera Sharadhuli I (Malaria Journal, 2008)
Abstract Background Although recent reports on congenital malaria suggest that the incidence is increasing, it is difficult to determine whether the clinical disease is due to parasites acquired before delivery or as a result of contamination by maternal blood at birth. Understanding of the method of parasite acquisition is important for estimating the time incidence of congenital malaria and design of preventive measures. The aim of this study was to determine whether the first Plasmodium falciparum malaria disease in infants is due to same parasites present on the placenta at birth. Methods Babies born to mothers with P. falciparum parasites on the placenta detected by PCR were followed up to two years and observed for malaria episodes. Paired placental and infant peripheral blood samples at first malaria episode within first three months of life were genotyped (msp2) to determine genetic relatedness. Selected amplifications from nested PCR were sequenced and compared between pairs. Results Eighteen (19.1%) out of 95 infants who were followed up developed clinical malaria within the first three months of age. Eight pairs (60%) out of 14 pairs of sequenced placental and cord samples were genetically related while six (40%) were genetically unrelated. One pair (14.3%) out of seven pairs of sequenced placental and infants samples were genetically related. In addition, infants born from primigravidae mothers were more likely to be infected with P. falciparum (P < 0.001) as compared to infants from secundigravidae and multigravidae mothers during the two years of follow up. Infants from multigravidae mothers got the first P. falciparum infection earlier than those from secundigravidae and primigravidae mothers (RR = 1.43). Conclusion Plasmodium falciparum malaria parasites present on the placenta as detected by PCR are more likely to result in clinical disease (congenital malaria) in the infant during the first three months of life. However, sequencing data seem to question the validity of this likelihood. Therefore, the relationship between placental parasites and first clinical disease need to be confirmed in larger studies.